1968
DOI: 10.1246/bcsj.41.2234
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Oxidation of Ferrous Ions Induced by Chelation

Abstract: The oxidation of ferrous ions by dissolved oxygen in aqueous solutions in the presence of such chelating agents as EDTA, DTPA, EDTAOH, EDTP, CyDTA and NTA was studied spectrophotometrically. The rate equation for the oxidation reaction is: d[Fe^III]/dt=4k_p[Fe^IIHZ][O_2]+4k_n[Fe^IIZ][O_2] where kp is the rate constant for the (1) reaction; kn, the rate constant for the (2) reaction; FeIIHZ, protonated chelate, and FeIIZ, the normal chelate. &Fe^IIHZ+O_2\xrightar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 6 publications
2
47
0
Order By: Relevance
“…In both cases, the chemical reaction of Fe" -EDTA and 0? is fast, as expected (52 Fig. 1 (converting f to [Fe,]).…”
Section: Photochen7iccil Rlissolirtiorzsupporting
confidence: 80%
“…In both cases, the chemical reaction of Fe" -EDTA and 0? is fast, as expected (52 Fig. 1 (converting f to [Fe,]).…”
Section: Photochen7iccil Rlissolirtiorzsupporting
confidence: 80%
“…Model results suggest that the loss of Fe(II)L 2 from the system proceeds at a rate of 3 Â 10 À3 s À1 , which may be due to O 2 -mediated oxidation with an apparent rate constant of k app = 12 L mol À1 s À1 , through rate limiting dissociation to form Fe(II)L 1 or perhaps a combination of these processes. Kurimura et al (1968) has reported an O 2 -mediated oxidation rate for the Fe(II)-DTPA complex of 7.0 L mol À1 s À1 and similarly Santana-Casiano et al (2004) have reported that Fe(II)-phthalate complexes are not readily oxidized by O 2 (k ox = (1 ± 1) Â 10 À3 L mol À1 s À1 ).…”
Section: One-ligand Class Modelmentioning
confidence: 98%
“…This experiment was exactly like experiment 3A except Fe3+BPDS replaced the 4'FeEDTA. The measurement of reduction of FeEDTA by trapping Fe2+ as FeBPDS3 necessarily underestimates the rate of reduction because EDTA catalyzes oxidation of Fe2- (21). Use of Fe+0-BPDS as the source of Fe?+ precludes the oxidative back reaction.…”
mentioning
confidence: 99%